Exploring market opportunities for African smallholders - Diao, Xinshen; Hazell, Peter B. R. (International Food Policy Research Institute, 2004)
Wealthy countries’ agricultural subsidies have also created unfair competition. African farmers not only have limited access to rich-country agricultural markets, but they also face unfair competition in their own domestic markets from subsidized imports of food staples. New challenges come from dramatically changed marketing chains that require African farmers to compete in markets that are more demanding in terms of product quality and food safety. What can be done to enhance market opportunities so that agriculture can become a more powerful engine of growth for the continent? Which markets and which products offer the greatest potential for raising incomes and food consumption? This brief addresses these questions and suggests policies that could help enlarge markets for African farmers.